208k views
0 votes
Hi. I need help with these questions.
See image for question.

Hi. I need help with these questions. See image for question.-example-1
User Bdfy
by
6.3k points

2 Answers

1 vote

Answer:

  • a) 3
  • b) 15

Explanation:

Given

  • P(x) = x³ + 4x² - 3x + 1

Find

  • a) P( 1 ), b) P( - 2)

Solution

Substitute the value of x:

a) P(x) = x³ + 4x² - 3x + 1

  • P(1) = 1³ + 4(1)² - 3(1) + 1 = 1 + 4 - 3 + 1 = 3
  • P(1) = 3

b) P(x) = x³ + 4x² - 3x + 1

  • P(-2) = (-2)³ + 4(-2)² - 3(-2) + 1 = -8 + 16 + 6 + 1 = 15
  • P(-2) = 15
User Donald A Nummer Jr
by
5.8k points
6 votes

Answer:

(a) P(1) = 3

(b) P(-2) = 15

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Function Notation

Explanation:

Step 1: Define

P(x) = x³ + 4x² - 3x + 1

P(1) is x = 1

P(-2) is x = -2

Step 2: Evaluate

P(1)

  1. Substitute: P(1) = 1³ + 4(1)² - 3(1) + 1
  2. Exponents: P(1) = 1 + 4(1) - 3(1) + 1
  3. Multiply: P(1) = 1 + 4 - 3 + 1
  4. Add: P(1) = 5 - 3 + 1
  5. Subtract: P(1) = 2 + 1
  6. Add: P(1) = 3

P(-2)

  1. Substitute: P(-2) = (-2)³ + 4(-2)² - 3(-2) + 1
  2. Exponents: P(-2) = -8 + 4(4) - 3(-2) + 1
  3. Multiply: P(-2) = -8 + 16 + 6 + 1
  4. Add: P(-2) = 8 + 6 + 1
  5. Add: P(-2) = 14 + 1
  6. Add: P(-2) = 15
User Henryk
by
6.1k points